Measuring Indonesian Intention to Use Islamic Mortgage: A Quantitative Approach - Rahmawan , Muhammad Diandra; Pradana , Mahir; Yunani, Akhmad (Journal of Ecohumanism, 2025)
This study explores the factors that influence the intention to use Islamic mortgage products in Indonesia, specifically focusing on Brand Awareness, Risk Perception, Religiosity, and their impact on Intention to Use. Using quantitative methods, 200 respondents were surveyed to gauge their interest in using Islamic mortgage products. The analysis used Structural Equation Modeling (SEM) through SmartPLS to evaluate the relationship between the variables. The findings show that Brand Awareness plays the most important role in shaping consumers' intention to use Islamic mortgage products, with a path coefficient of 0.773, which indicates a strong and significant influence. Perceived Risk also significantly influences Brand Awareness (β = 0.689), highlighting that consumers' perception of risk can shape their awareness of Islamic mortgage options, although its direct impact on Intention to Use is relatively smaller (β = 0.118). In addition, Religiosity was found to have a meaningful yet moderate influence on Brand Awareness (β = 0.275) and Intention to Use (β = 0.085), underscoring the relevance of religious values in consumers' decision-making process. Overall, the results suggest that to increase the adoption of Islamic mortgage products in Indonesia, financial institutions should focus on increasing Brand Awareness, reducing Perceived Risk, and increasing the religiosity of their target audience. Marketing strategies that emphasize Shariah compliance, transparency, and ethical financial practices can encourage the intention to use Islamic mortgages, thereby contributing to the growth of the Islamic financial sector in Indonesia.